Estudio De Viabilidad Para La Producción Y Comercialización De Bolsos Ecológicos A Base De Yute “Producto Molan” (2022)
In principle, the of this monograph is to carry out the feasibility study of the new line of MOLAN products from the Fahyol company, which seeks to satisfy the needs and tastes of people, will be carried out through a financial and market study. at the national level, which is expected in a first stage to be commercialized in the local market (Bogotá D.C), as a second stage to achieve regional expansion (Colombia) and in a final stage the export of this product worldwide. All of the above, based on the excellent quality of the product and the novelty in the manufacturing material, since in its production process the JUTE-based fabric is used as the main material; since it is a 100% biodegradable and recyclable textile, therefore, harmless to the environment (United Nations Organization for Food and Agriculture, 2022)